A pharmacognostical study of farsetia aegyptia turra family : Cruciferae growing in Egypt - Walaa Maged Ismail Elkot; Ahlam Mahmoud Elfishawy; Amira Ahmed Abdelmotaal; Nadia Mohamed Sokkar (Cairo : Walaa Maged Ismail Elkot, 2012)
Botanical study and DNA fingerprint : macromorphological micromorphological study and DNA fingerprint of the plant . Biological study : Determination of the safety of the plant extracts, the antiiflammatory , hepatoprotective , antioxidant , anti - diabetic and anticancer activities . Phytochemical study: preliminary phytochemical screening , the lipioidal content , the mucilage content , the glucosinolate hydrolysis products , the phenolic content and investigation of the methylene chloride and the ethyl acetate fraction of the root
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Biological; Botanical study; DNA